Implementasi Manajemen Berbasis Madrasah dalam Upaya Peningkatan Mutu Pendidikan di Pondok Pesantren Harisul Khairaat Bumi Hijrah Tidore Provinsi Maluku Utara - Andy Andy (IAIN Manado, 2021)
Implementation of Madrasa-Based Management in Efforts to Improve the Quality of Education at the Harisul Khairaat Islamic Boarding School in Bumi Hijrah Tidore, North Maluku. This paper describes the implementation of madrasah-based management to improve the quality of education at the Harisul Khairaat Bumi Hijrah Islamic Boarding School. This research is descriptive qualitative research. Data collection techniques are interviews, observation, and documentation techniques.The results of this study indicate that: (1) The quality of madrasa education at the Harisul Khairaat Islamic Boarding School with the implementation of MBM has had a positive impact on the input, process, and output of education. abroad and alumni are distributed in the world of work. (2) The implementation of madrasa-based management at the Harisul Khairaat Bumi Hijrah Islamic Boarding School has been carried out by applicable regulations